A Study of China's No-First-Use Policy on Nuclear Weapons. Issue 1 (2nd January 2018) - Pan, Zhenqiang
ABSTRACT: China's no-first-use policy implies that the country possesses nuclear weapons only to deter other states from a nuclear attack. It expresses the purely self-defensive nature of China's nuclear strategy. The no-first-use policy has effectively helped China to establish a moderate nuclear capability that is adequate to deal with nuclear threats from the outside and to maintain a delicate strategic balance. The policy has also contributed to strategic stability particularly in the Asia-Pacific region. More fundamentally, it has demonstrated a viable path toward international nuclear disarmament. Although it appears that China will most likely to continue to stick to its pledge of the no-first-use in the foreseeable future, the fate of the policy hinges, in a large part, on the evolution of China–US relations in the growing major power competition. China's serious rift with non-nuclear weapon states on the role of nuclear weapon may also have important bearings on its no-first-use policy. Ultimately, the real question for China is whether it has the strategic vision and political courage to realize the limits of its no-first-use policy in the twenty-first century, go beyond this commitment, and take the lead in the world efforts to reduce and eliminate the role of nuclear weapons in the military strategies of any powers so as to pave the way for the complete prohibition and thorough destruction of all nuclear weapons.